Pattern: Set ground rules - Garcia, M.P.; Kern, Nergiz; Serrano, R.; Warburton, S. (Sense Publishers, 2014)
Laying the foundation for productive interaction and participation within synchronous text based chat sessions. © 2014 Sense Publishers. All Rights Reserved.
Keywords: [No Kerywords]